BUSINESS PLAN BAGI PENGUSAHA TAHU DI TENGAH NAIKNYA HARGA MINYAK GORENG DAN KEDELAI - Rina Sari Qurniawati (ABDI MAKARTI, 2022)
This activity aims to provide entrepreneurs with an understanding of the importance of having a business plan to improve their entrepreneurial skills. The output target of this activity is that tofu entrepreneurs are expected to be able to grow creative ideas and innovations so that their businesses can grow. The method of activities carried out by the community service team is carried out in two stages, namely the method of collecting data through interviews and observations and then making a business plan together.